Impaired Bone Fracture Healing in Type 2 Diabetes Is Caused by Defective Functions of Skeletal Progenitor Cells. Issue 2 (19th January 2022) - Figeac, Florence; Tencerova, Michaela; Ali, Dalia; Andersen, Thomas L; Appadoo, Dan Rémi Christiansen; Kerckhofs, Greet; Ditzel, Nicholas; Kowal, Justyna M; Rauch, Alexander; Kassem, Moustapha
Abstract: The mechanisms of obesity and type 2 diabetes (T2D)-associated impaired fracture healing are poorly studied. In a murine model of T2D reflecting both hyperinsulinemia induced by high-fat diet and insulinopenia induced by treatment with streptozotocin, we examined bone healing in a tibia cortical bone defect. A delayed bone healing was observed during hyperinsulinemia as newly formed bone was reduced by –28.4 ± 7.7% and was associated with accumulation of marrow adipocytes at the defect site +124.06 ± 38.71%, and increased density of SCA1+ (+74.99 ± 29.19%) but not Runx2 + osteoprogenitor cells. We also observed increased in reactive oxygen species production (+101.82 ± 33.05%), senescence gene signature (≈106.66 ± 34.03%), and LAMIN B1 - senescent cell density (+225.18 ± 43.15%), suggesting accelerated senescence phenotype. During insulinopenia, a more pronounced delayed bone healing was observed with decreased newly formed bone to –34.9 ± 6.2% which was inversely correlated with glucose levels ( R 2 = 0.48, P < .004) and callus adipose tissue area ( R 2 = .3711, P < .01). Finally, to investigate the relevance to human physiology, we observed that sera from obese and T2D subjects had disease state-specific inhibitory effects on osteoblast-related gene signatures in human bone marrow stromal cells which resulted in inhibition of osteoblast and enhanced adipocyte differentiation. Our data demonstrate that T2D exerts negative effects on bone healing through inhibition of osteoblast differentiation of skeletal stem cells and induction of accelerated bone senescence and that the hyperglycemia per se and not just insulin levels is detrimental for bone healing. Graphical Abstract: